Peran Perempuan dalam Merebut Ruang Hidup: Studi Ekofeminisme Tentang Perlawanan Perempuan di Banjar Selasih, Bali - Annajmatul Istiqlali (Jurnal Ilmu Sosial Indonesia (JISI), 2022)
Abstract. This article aims to identify the role and resistance of Banjar Selasih women in land grabbing conflicts and the struggle for living space through ecofeminism studies. Specifically, the author wants to see how far the contribution of ecofeminism in explaining the domination and discrimination experienced by both the environment and women, with the assumption that these conditions originate from the same problem, namely, patriarchal culture. So that the struggle carried out by Banjar Selasih women for the earth is actually included in the struggle for social-ecological justice and equality. Using a qualitative case study approach, this study indicated that there are factors behind the active participation of Banjar Selasih women in the struggle for living space such as caring for and maintaining, maintaining culture and customs, rejection of domination, and emancipation from tradition which the author then examines through ecofeminism studies with the assumption that feminism and ecology movements actually have mutually reinforcing goals, both want to build a view of the world and its practice that is not based on domination.Keywords: Ecofeminism, Women's Role, Women’s Living Space Dispute, Women's Resistance, Land deprivation. Abstrak. Artikel ini bertujuan untuk mengidentifikasi peran dan perlawanan perempuan Banjar Selasih dalam konflik perampasan tanah dan perebutan ruang hidup melalui studi ekofeminisme. Secara spesifik penulis akan melihat sejauh mana studi ekofeminisme dapat menjelaskan dominasi serta diskriminasi yang dialami baik oleh lingkungan hidup maupun perempuan, dengan dugaan bahwa kondisi tersebut bersumber dari problem yang sama yakni budaya patriarki. Sehingga perjuangan yang dilakukan oleh perempuan Banjar Selasih untuk bumi sejatinya termasuk ke dalam perjuangan demi keadilan dan kesetaraan sosial-ekologis. Melalui studi kasus kualitatif, studi ini menemukan bahwa terdapat faktor yang melatarbelakangi aktifnya perempuan Banjar Selasih dalam upaya perebutan ruang hidup seperti merawat dan memelihara, menjaga budaya dan adat, penolakan atas dominasi, serta emansipasi dari tradisi. Melalui studi ekofeminisme penulis menyimpulkan bahwa gerakan feminisme dan ekologi sejatinya mempunyai tujuan yang saling memperkuat. Keduanya hendak membangun pandangan terhadap dunia yang tidak berdasarkan dominasi.Kata Kunci: Ekofeminisme, Peran Perempuan, Perebutan Ruang hidup, Perlawanan Perempuan, Perampasan tanah.